GIS-based suitability mapping for Sargassum mariculture in the eastern coast of Southern Leyte - Lasquites, Juztine Jane S.
Sargassum is one of the important brown seaweeds distributed in temperate and tropical oceans. It is utilized as animal feed, fertilizer, source of alginate for industrial uses, raw material for ethanol production, breeding grounds for other marine species and for human consumption as sea vegetables and seaweed herbs. Due to its high commercial value, harvesting of the seaweed in the Philippines was uncontrolled until the Department of Agriculture regulated the collection and harvesting of this seaweed. Seasonal restrictions were imposed except in developed culture facilities for Sargassum. Therefore, the need to identify areas suitable for mariculture of the seaweed is vital to address the demand on both local and global markets while maintaining ecological balance in the marine ecosystem. Multi-Criteria Decision Analysis using Fuzzy AHP was used to integrate six (6) parameters, namely, wind speed, surface current, sea surface salinity (SSS), sea surface temperature (SST), day minus tide and depth. Precautionary or restricted areas such as marine protected areas and recreational beaches were also considered in generating the suitability map. These parameters were identified based on the studies of Nirmala, et.al. (2014), Quiñones-Vitches, et.al. (2015) and Yulianto, et.al. (2017) for site suitability of seaweed mariculture. Sea surface temperature obtained the highest weight (27%) based on the average Fuzzy AHP ratings from five (5) experts; while depth and wind speed obtained the least weight at 8%. Suitable areas for Sargassum mariculture are located predominantly in the coast of Silago from Brgy. Hingatungan to Brgy. Balagawan. Furthermore, suitable areas for Sargassum mariculture can also be found in the northern and eastern part of San Pedro. The suitability of these sites is highly sensitive to changes in surface current, SSS and SST. Hence, small changes of these parameters will greatly affect the area covered by those classified as suitable for Sargassum mariculture.